Pengaruh Penerapan Budaya Literasi terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VII MTSN 10 Blitar - Nafiatul Fitria; Bagus Setiawan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Based on a number of variables, including inadequate reading awareness, this study demonstrates how the use of literacy culture impacts learning outcomes in social studies courses, resulting in less than ideal learning outcomes. 38 students make up the sample for this quantitative investigation. Finding out how the implementation of literacy culture affects student learning results and how much of an impact it has on the learning outcomes of class VII students at MTSN 10 Blitar are the goals of this study. ‎ According to the study's findings, the T-test yielded a Sig value of 0.000 ‎‎<0.05, indicating a significant relationship between the application of literacy culture and learning outcomes in social studies courses. The impact of literacy culture on learning outcomes is 17.9%. In the meantime, other factors not covered in this study have an impact on the remaining 82.1%. Together with the F-statistic analysis results of 0.031 ‎‎<0.05, it can be said that student learning outcomes are statistically impacted by literacy culture. ‎